The Power of Cliques, Friendships, and Social Networks in Strengthening Adult Basic Education Student Persistence and Retention - Jeff Zacharakis (Adult Education Research Conference, 2010)
This issue of student persistence and retention continues to plague most adult learning centers. This paper develops a theoretical perspective that uses social capital and network theory to explain why some students succeed in an ABE/GED program and go on to pursue post-secondary education and why some do not.